(untitled) (Research, Society and Development, 2021)
Objective: Demonstrating the importance of the creation of Marabá Diabetic Foot Reference Center (CRPDM in Portuguese) for the city and region. Methodology: This is a cross-sectional, observational, retrospective study conducted at a general hospital in the city of Marabá-PA, Brazil. The study population is consisted of patients treated by the Vascular Surgery Department at the Hospital Municipal de Marabá, from April 2015 to September 2019. Results: It was identified a high number of healthcare services in the period in the department of vascular surgery. A total of 621 services were provided with the predominance of surgical procedures (51%), including amputations and stump revisions and patients diagnosed with diabetes. Regarding gender there was a male prevalence and considering origin 85% of the patients were from Marabá. Conclusion: In view of that, the CRPDM aims to implement a reference service for diabetic patients, based on the protocols and recommendations of the Ministério da Saúde (Federal Health Ministry), Sociedade Brasileira de Diabetes – SBD (Brazilian Diabetes Society), and International Working Group on the Diabetic Foot (IWGDF). The perspective is to change the reality of the city and region of Marabá, promoting improvements in care to reduce complications and sequelae in this population.